Prevalence and treatment implications of ICD-11 complex PTSD in Australian treatment-seeking current and ex-serving military members. Issue 1 (1st January 2021) - Howard, Alexandra; Agathos, James A.; Phelps, Andrea; Cowlishaw, Sean; Terhaag, Sonia; Arjmand, Hussein-Abdullah; Armstrong, Renee; Berle, David; Steel, Zachary; Brewer, Douglas; Human, Berquin; Herwig, Andrea; et al.
ABSTRACT: Background : Despite growing support for the distinction between posttraumatic stress disorder (PTSD) and complex PTSD (CPTSD) as separate diagnoses within the ICD-11 psychiatric taxonomy, the prevalence and treatment implications of CPTSD among current and ex-serving military members have not been established. Objective : The study aims were to a) establish the prevalence of provisional ICD-11 CPTSD diagnosis relative to PTSD in an Australian sample of treatment-seeking current and ex-serving military members, and b) examine the implications of CPTSD diagnosis for intake profile and treatment response. Methods : The study analysed data collected routinely from Australian-accredited treatment programmes for military-related PTSD. Participants were 480 current and ex-serving military members in this programmes who received a provisional ICD-11 diagnosis of PTSD or CPTSD at intake using proxy measures. Measures of PTSD symptoms, disturbances in self-organisation, psychological distress, mental health and social relationships were considered at treatment intake, discharge, and 3-month follow-up. Results : Among participants with a provisional ICD-11 diagnosis, 78.2% were classified as having CPTSD, while 21.8% were classified as having PTSD. When compared to ICD-11 PTSD, participants with CPTSD reported greater symptom severity and psychological distress at intake, and lower scores on relationship and mental health dimensions of the quality of life measure. These relative differences persisted at each post-treatment assessment. Decreases in PTSD symptoms between intake and discharge were similar across PTSD (d RM  = −0.81) and CPTSD (d RM  = −0.76) groups, and there were no significant post-treatment differences between groups when controlling for initial scores. Conclusions : CPTSD is common among treatment-seeking current and ex-serving military members, and is associated with initially higher levels of psychiatric severity, which persist over time. Participants with CPTSD were equally responsive to PTSD treatment; however, the tendency for those with CPTSD to remain highly symptomatic post-treatment suggests additional treatment components should be considered. HIGHLIGHTS: ICD-11 complex PTSD (CPTSD) is more prevalent than PTSD in current and ex-serving military members seeking treatment for PTSD. Responses to programmatic trauma-focused treatment were similar across the two provisional diagnoses. Participants with CPTSD maintained higher symptom severity overall post-treatment than those with PTSD, and further research is needed to establish what supplementary treatment might be appropriate. CPTSD is more prevalent than PTSD in treatment-seeking current and ex-serving military members. Participants with CPTSD were equally responsive as those with PTSD to trauma-focused treatment, though those with CPTSD maintained higher symptom severity pre- and post-treatment.